Strumenti d’osservazione per il telerilevamento da satellite - Perrotta, Giorgio (GEOmedia, 2009)
Earth observation instruments for satellite remote sensing This article features a brief description of the instrumentation families commonly used during Earth Observation activities. The optical exploration of our planet, already anticipated more than 50 years ago at the beginning of the exploration era with the first analogic photographic instrumentation, is now complemented by sophisticated instruments that work under the domain of radio waves in order to produce informations useful fo a wide variety of applications.